2023
DOI: 10.3390/nu15061355
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Probiotic Properties of Bifidobacterium animalis subsp. lactis SF and Its Alleviating Effect on Non-Alcoholic Fatty Liver Disease

Abstract: Nonalcoholic fatty liver disease (NAFLD) is a common chronic liver disease with many influencing factors. With the increasing role of the gut–liver axis in various liver diseases, research on the prevention and treatment of NAFLD with probiotics is increasing. In the present study, a Bifidobacterium animalis subsp. strain, B. lactis SF, was isolated from the feces of healthy infants and characterized by sequencing of the 16S rDNA. A systematic probiotic evaluation was carried out, and a diet-induced mouse mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…Collectively, the articles reviewed in this study all aligned in the same direction: Bifidobacterium acts beneficially as a probiotic in NAFLD, ALD, and Cirrhosis. It does so by restoring the intestinal microbiota balance, reducing inflammation and oxidative [23,[28][29][30], whereas (B) represents the same for animal studies [19][20][21][22][24][25][26][27]. The letter "D" denotes the domains present in the checklists.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Collectively, the articles reviewed in this study all aligned in the same direction: Bifidobacterium acts beneficially as a probiotic in NAFLD, ALD, and Cirrhosis. It does so by restoring the intestinal microbiota balance, reducing inflammation and oxidative [23,[28][29][30], whereas (B) represents the same for animal studies [19][20][21][22][24][25][26][27]. The letter "D" denotes the domains present in the checklists.…”
Section: Discussionmentioning
confidence: 99%
“…These data were accompanied by improvements in biochemical parameters such as the antioxidant molecules catalase (CAT), glutathione (GSH), superoxide dismutase (SOD), and malondialdehyde (MDA). Therefore, there was a significant improvement in immune balance, intestinal mucosal health, and hepatic metabolism [26][27][28][29][30].…”
Section: Bifidobacterium In Nafldmentioning
confidence: 99%
“…The results demonstrated that Lactobacillus SF could restore gut microbiota balance by increasing the relative abundance of bacteria capable of occupying the same ecological niche as pathogenic bacteria, thereby reducing the survival space for pathogens. This indicates that Lactobacillus SF exhibits excellent resistance to gastric fluids, colonization in the intestine, and strong antibacterial and antioxidant capabilities ( 84 ).…”
Section: Interaction Between Microbiota and Bacteriophages In Ibdmentioning
confidence: 99%
“…Probiotic supplementation may facilitate gut microbiota homeostasis, enhance intestinal barrier integrity, and attenuate pro-inflammatory cytokine production in MAFLD patients. Several specific strains of probiotics, such as Lactobacillus kefiranofaciens ZW3 [ 106 ], Lactobacillus rhamnosus and Pediococcus acidilactici [ 107 ], Bifidobacterium adolescentis [ 108 , 109 ], and Grifola frondosa [ 110 ] are considered to treat MAFLD by inhibiting the TLR4/MyD88/JNK/NF-κB/TRAF6/NLRP3 pathway, reducing the release of inflammatory factors, improving IR, and restoring lipid metabolism. Probiotic derivatives may also exert anti-MAFLD effects.…”
Section: Therapeutic Strategies For Mafld Targeting Tlr4 Signaling Pa...mentioning
confidence: 99%